The Involvement of Glycosaminoglycans in Airway Disease Associated with Cystic Fibrosis - Emer P. Reeves; David A. Bergin; Michelle A. Murray; Noel G. McElvaney (The Scientific World Journal)
Individuals with cystic fibrosis (CF) present with severe airway destruction and extensive bronchiectasis. It has been assumed that these structural airway changes have occurred secondary to infection and inflammation, but recent studies suggest that glycosaminoglycan (GAG) remodelling may be an important independent parallel process. Evidence is accumulating that not only the concentration, but also sulphation of GAGs is markedly increased in CF bronchial cells and tissues. Increased expression of GAGs and, in particular, heparan sulphate, has been linked to a sustained inflammatory response and neutrophil recruitment to the CF airways. This present review discusses the biological role of GAGs in the lung, as well as their involvement in CF respiratory disease, and their potential as therapeutic targets.